Data Integration Through Cirebon One Data - Cerrly, Cerrly; As-syahrani, Nadia Safitri; Nursahidin, Nursahidin; Sutarjo, Moh. (PT FORMOSA CENDEKIA GLOBAL, 2025)
Digital transformation enhances public service and government efficiency. Indonesia’s One Data Regulation supports integrated and quality data management. This qualitative policy study examines the implementation of the Cirebon One Data Policy using George C. Edward III’s framework (communication, resources, disposition, bureaucratic structure). Data were collected through interviews with Cirebon City DKIS officials. Findings indicate suboptimal implementation. Communication delays hinder data updates. Limited human resources and overlapping roles affect efficiency. Although data guardians show strong commitment, lack of sanctions weakens enforcement. Bureaucratic challenges arise from changing standards and limited data use. Despite efforts like technical training and evaluations by DKIS, several issues impede effective implementation. Improved coordination, enforcement mechanisms, and resource allocation are needed to optimize the Cirebon One Data Policy.